The Moral Concepts of Peta Kapanca Ceremony in Bima Community - Yono Yono; Sutisna Sutisna; Supriyanto Supriyanto; Amrin Amrin (Buletin Al-Turas, 2023)
PurposeThis article aimed to examine the moral concepts of peta kapanca ceremony as a tradition of the Bima people at every wedding ceremony.MethodThis study used an exploratory case study design which mainly depended so much on qualitative taken directly in the Bima Community of West Nusa Tenggara. The data collection applied observation, interviews and documentation and a literature study. In analyzing the data, it used classical hermeneutics and sociology. In addition, the study implemented data reduction, data presentation, and drawing conclusions stages of analysis.Results/findingsThe results showed that peta kapanca ceremony in the marriage of the Bima community had moral values, comprising how to worship Allah, how to behave and treat oneself and his family and how to behave and treat the society.ConclusionThe values contained in the peta kapanca are very relevant to the values in Islamic teachings. Thus, it is necessary for the Bima Regency government, community leaders, traditional leaders, and all levels of Bima society and the younger generation to increase awareness of the importance of preserving and caring for peta kapanca tradition and other local cultural traditions, so that they can grow and develop in line with the Islamic teachings and local wisdoms of Mbojo tribe in Bima.